Altered structural and functional homotopic connectivity associated with the progression from mild cognitive impairment to Alzheimer's disease. (January 2023) - Chen, Shanshan; Wu, Huimin; Song, Yu; Ge, Honglin; Yan, Zheng; Xue, Chen; Qi, Wenzhang; Yuan, Qianian; Lin, Xingjian; Chen, Jiu; ,
Highlights: Structural and functional inter-hemispheric alteration were blank in progressive MCI and stable MCI. Decreased homotopic connectivity was associated with cognitive impairment and corpus callosum atrophy. The corpus callosum atrophy partially mediates the relationship between the reduction of homotopic connectivity and cognitive impairment. Abstract: The progressive mild cognitive impairment (pMCI) is associated with an increased risk of Alzheimer's disease (AD). Many studies have reported the disrupted brain alteration during the imminent conversion from pMCI to AD. However, the subtle difference of structural and functional of inter-hemispheric between pMCI and stable mild cognitive impairment (sMCI) remains unknown. In the present study, we scanned the multimodal magnetic resonance imaging of 38 sMCI, 26 pMCI, and 50 healthy controls (HC) and assessed the cognitive function. The voxel-mirrored homotopic connectivity (VMHC) and volume of corpus callosum were calculated. A structural equation modeling (SEM) was established to determine the relationships between the corpus callosum, the inter-hemispheric connectivity, and cognitive assessment. Compared to sMCI, pMCI exhibited decreased VMHC in insular and thalamus, and reduced volume of corpus callosum. SEM results showed that decreased inter-hemispheric connectivity was directly associated with cognitive impairment and corpus callosum atrophy, and corpus callosum atrophy indirectly caused cognitive impairment by mediating inter-hemispheric connectivity in pMCI. In conclusion, the destruction of homotopic connectivity is related to cognitive impairment, and the corpus callosum atrophy partially mediates the association between the homotopic connectivity and cognitive impairment in pMCI.